2019
DOI: 10.1007/s12559-019-09649-9
|View full text |Cite
|
Sign up to set email alerts
|

Word Spotting in Background Music: a Behavioural Study

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Several studies present small samples of adult participants, making it difficult to generalize the results to the general adult population (≤24 adult participants; Amezcua et al, 2005 ; Speer, 2011 ; Giannouli, 2012 ; Fernandez et al, 2019 ; Cloutier et al, 2020 ). In addition, most of the time, non-auditory (e.g., silence) and auditory (e.g., noises with sound characteristics similar to those of music) control conditions were lacking ( Darrow et al, 2006 ; Marchegiani and Fafoutis, 2019 ; Deng and Wu, 2020 ; Cloutier et al, 2020 ). There were also methodological limitations regarding the choice of the sound material used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies present small samples of adult participants, making it difficult to generalize the results to the general adult population (≤24 adult participants; Amezcua et al, 2005 ; Speer, 2011 ; Giannouli, 2012 ; Fernandez et al, 2019 ; Cloutier et al, 2020 ). In addition, most of the time, non-auditory (e.g., silence) and auditory (e.g., noises with sound characteristics similar to those of music) control conditions were lacking ( Darrow et al, 2006 ; Marchegiani and Fafoutis, 2019 ; Deng and Wu, 2020 ; Cloutier et al, 2020 ). There were also methodological limitations regarding the choice of the sound material used.…”
Section: Introductionmentioning
confidence: 99%
“…There were also methodological limitations regarding the choice of the sound material used. For example, some studies have presented music with words (e.g., Darrow et al, 2006 ; Speer, 2011 ; Marchegiani and Fafoutis, 2019 ; Deng and Wu, 2020 ), which has generally resulted in a deleterious effect on performance. However, several studies have previously shown that the presence of speech or words in a sound environment tends to negatively affect cognitive performance in comparison with a speechless sound environment (e.g., Salamé and Baddeley, 1989 ; Szalma and Hancock, 2011 ).…”
Section: Introductionmentioning
confidence: 99%